(untitled) (Research, Society and Development, 2021)
Introduction: breast milk is the ideal food for children, especially exclusively, in the first six months of life and supplemented after up to two years of age or more1. Currently, another new challenge presents itself for the promotion of breastfeeding: the COVID-19 pandemic. Objective: to map the scientific production that favors the promotion of breastfeeding in the COVID-19 pandemic. Methods: scoping review developed based on the international PRISMA-ScR guide and the method proposed by the Joanna Briggs Institute. The survey was conducted in August 2021 in scientific databases and gray literature. Data were collected, analyzed and synthesized in a narrative way. Results: 2466 publications were surveyed, 18 of which were selected. The publications point to the low possibility of vertical transmission of COVID-19 or through breastfeeding and also demonstrate the incipient amount of scientific evidence on the subject. Conclusion: breastfeeding, even in the context of SARS-CoV-2 infection, must be promoted and further studies are needed to establish, with significant scientific evidence, the safety of breastfeeding in the context of COVID-19.